Assessing Sociodemographic Variances, COVID-19 Knowledge, and Health Practices in Intervention versus Non-Intervention Settings - Gupta, Mithun (Journal of Current Health Sciences, 2025)
Bangladesh's response to the WHO’s declaration of COVID-19 as a global pandemic on March 11, 2020, exposed key gaps in public trust, coordination, and community engagement. To address these challenges and promote awareness and adoption of preventive behaviors, BRAC and the CDC Foundation launched a community-based intervention in Gazipur district. This quasi-experimental study employed a mixed-methods approach using a pre-test post-test control group design to evaluate the initiative's impact. Quantitative data were collected through baseline and endline surveys in intervention (Ward-26) and control (Ward-25) areas, with 611 participants surveyed at each site. Knowledge and practices regarding COVID-19 transmission, mask usage, hand hygiene, and social distancing were assessed. Descriptive statistics and the Difference-in-Differences (DiD) method were applied to examine changes over time. Findings revealed an increase in awareness within the intervention group—for example, knowledge of droplet transmission rose from 75% to 84%—while the control group showed declines. However, actual adherence to preventive practices declined over time, including mask-wearing (from 93% to 86%) and social distancing, particularly in crowded public areas. Qualitative findings from interviews and field observations highlighted contributing factors such as discomfort, financial pressures, reduced fear of COVID-19, and sociocultural norms. Although the intervention improved awareness and infrastructure, sustained behavior change was hindered by community fatigue, prolonged restrictions, and weak enforcement. In conclusion, the program enhanced public knowledge but failed to ensure lasting preventive behaviors. Future efforts should emphasize community engagement, consistent enforcement, and adaptive awareness strategies to strengthen pandemic preparedness.